European Research on Electrochemotherapy in Head and Neck Cancer (EURECA) project: Results of the treatment of skin cancer. (August 2016) - Bertino, Giulia; Sersa, Gregor; De Terlizzi, Francesca; Occhini, Antonio; Plaschke, Christina Caroline; Groselj, Ales; Langdon, Cristobal; Grau, Juan J.; McCaul, James A.; Heuveling, Derrek; Cemazar, Maja; Strojan, Primoz; et al.
Abstract: Electrochemotherapy is an effective and safe method for local treatment of cutaneous and subcutaneous tumours, where electric pulses cause increased permeability of cell membranes in the tumour mass, enabling dramatically enhanced effectiveness of bleomycin and other hydrophilic drugs. Here, we report results of a European multi-institutional prospective study of the effectiveness of electrochemotherapy in the treatment of skin cancer of the head and neck (HN) area, where standard treatments had either failed or were not deemed suitable or declined by the patient. A total of 105 patients affected by primary or recurrent skin cancer of the HN area were enrolled; of these, 99 were eligible for evaluation of tumour response. By far, the majority (82%) were treated only once, and 18% of patients had a second treatment. The objective response was highest for basal cell carcinoma (97%) and for other histologies was 74%. Small, primary, and treatment-naive carcinomas responded significantly better (p < 0.05), as investigated by univariate analysis. Electrochemotherapy was well tolerated and led to a significant improvement of quality of life, estimated by the European Organisation for Research and Treatment of Cancer quality of life questionnaires. At 1-year follow-up, the percentages of overall and disease-free survival were 76% and 89%, respectively. Electrochemotherapy is an effective option for skin cancers of the HN area and can be considered a feasible alternative to standard treatments when such an alternative is appropriate. The precise role for electrochemotherapy in the treatment algorithm for non-melanoma skin cancer of the HN region requires data from future randomised controlled studies. (ISRCTN registry N. 30427) Highlights: Electrochemotherapy is a local ablative treatment for tumour nodules. Electrochemotherapy utilises electroporation for enhanced drug delivery to cells. Electrochemotherapy is highly effective in recurrent and primary, small skin tumours. Electrochemotherapy guarantees limited side-effects and good cosmetic results.